2021
DOI: 10.2147/rmhp.s315262
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Associated Factors of Short Sleep Duration Among Nurses in Tertiary Public Hospitals in China: Findings from a National Survey

Abstract: Background Sleep is an essential component of health and well-being. Short sleep duration may negatively affect nurses’ health and patients’ safety. Objective To investigate the sleep duration and subjective satisfaction with sleep duration among nurses in tertiary public hospitals in China and to explore the associated factors. Methods This cross-sectional study was conducted between December 18 and 31, 2017 in 136 major public hospitals fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Therefore, aside from optimal support according to years of physiotherapy experience, appropriate support according to physiotherapist age should also be considered, which may include workload reduction among older HCPs in consideration of work environment and content. In line with this, a previous study had also found an association between short sleep duration and older age among HCPs [ 29 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Therefore, aside from optimal support according to years of physiotherapy experience, appropriate support according to physiotherapist age should also be considered, which may include workload reduction among older HCPs in consideration of work environment and content. In line with this, a previous study had also found an association between short sleep duration and older age among HCPs [ 29 ].…”
Section: Discussionsupporting
confidence: 85%
“…In the current study, 67.4% of the physiotherapists had an average sleep duration of ≤6 h. Short sleep duration in HCPs has been significantly associated with long work hours and increased workload [ 29 ]. During the COVID-19 pandemic, working in a high-risk environment, such as providing direct front-line care to patients with COVID-19, had been identified as a risk factor associated with insomnia [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A sleep duration time of less than 7 h is common in nurses and can result in dissatisfaction with sleep time (Liu et al., 2021); this may be due to short periods of rest between shifts which can reduce sleep duration and result in daytime sleepiness (Booker et al., 2018). The term ‘shift work disorder’, which can be caused by work hours that occur during normal sleep time, resulting in misalignment of an RNs circadian rhythm and their shift schedule (Cheng & Drake, 2019), can result in extreme tiredness and insomnia (Di Milia et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, regarding sharing activities on SNSs, younger adults had higher life satisfaction and lower loneliness, while older adults had the opposite [ 78 ]. However, previous meta-analyses found no substantial moderation in the association between time spent on SNSs and PWB [ 34 , 79 ]. It's necessary to examine how age influences the connection between global indicators of SNS use and SWB [ 80 ].…”
Section: Literature Reviewmentioning
confidence: 96%